AMERICAN’S FAMILYHOOD IN ARTHUR MILLER’S THE DEATH OF A SALESMAN - Harry Kurniawan (LINGUA LITERA : journal of english linguistics and literature, 2021)
Abstract Arthur Miller was known as an American Playwright who often consider put the theme of a man who has problems or struggles for his internal desire or the society or even his family in his work. This research shows Willy’s struggle as a father to his family’s prosperity. The writer used the sociological approach and Power theory from Michael Foucault to conduct the analysis. Foucault’s theories primarily talked about the relationship between power and knowledge, and how they are used as a form of social control through societal institutions. The writer concluded that in life Willy has a motto to tell his sons which is money is everything and in reality, that motto is not eligible because education is above everything especially in the working world. Willy is obsessed with power. After Willy chooses to do suicide to sacrifice for his family, it finally reveals that Willy is just a normal father who wants his sons to be successful people with his lead as a parent.